Immobilization of glucose oxidase/ferrocene carboxylic acid in composite silica sol-gel/cross-linked poly (vinyl alcohol)/nafion membrane - Jusoh, Norhana; Abdul Aziz, Azila (2006)
A method of tethering a mediator to an enzymatic membrane was studied to construct a non-leaking mediated glucose biosensor. Ferrocene carboxylic acid and glucose oxidase were immobilized in a sol gel derived silica (SGS) matrix containing cross-linked poly (vinyl alcohol) (CLPVA) and Nafion. CLPVA was applied as a solid support due to the ability to form very homogenous films with high quality. SGS was used to increase the encapsulation capacity for the enzyme and mediator. The presence of Nafion, a negatively charged polymer, not only prevented the cracking of pure sol-gel derived silica film but also improved the sensitivity and stability of the enzyme/mediator membrane by minimizing the leaching of the mediator. The biosensor response to glucose was evaluated amperometrically at 0.363V. The immobilization technique resulted in an enzyme/mediator membrane that was simple to cast, had minimal mediator and enzyme losses, worked under lower operating potentials and provided good responses over a wide range of concentrations.